Culture of canine epithelial cells for veterinarian therapy - Gómez-Murillo, Irene (2015)
We present the clinical case of a canine patient with a cutaneous trauma. The injure was treated with a heterologous transplant of in vitro cultured fibroblasts on a fibrinogen-based matrix gel. This resulted on a noticeable reduction on the wound size and the patient did not present any allergic reactions or adverse effects to the treatment. This experience opens an opportunity for the development of the veterinary Tissue Engineering area with therapeutic applications in Costa Rica.